PENGARUH KOMPETENSI GURU, PENDIDIKAN GURU, DAN BAHASA PEMBELAJARAN TERHADAP KINERJA SEKOLAH (Studi Kasus SMK Se Kota Karanganyar) - Lambangsari , Ike (2011)
This research purpose to analyze (1) influence of teacher interest, education of teacher, and study Ianguage to performance go to school in SMK Town Karanganyar. (2) influence of interest learn to performance go to school in SMK Town Karanganyar. (3) influence of education of teacher to performance go to school in SMK Town Karanganyar. (4) influence of study Ianguage to performance go to school in SMK Town Karanganyar. Research location is in entire SMK town Karanganyar. Reseach population is entire teachers of SMK town Karanganyar amount of 232 teachers. Samples taking as 139 teachers with propotionate stratified random sampling technique. Data collecting by using questionary. Data analysis technique uses double linear regression analysis (F test and t test) and classic asumption test (normality test, autorcorrelation test, heteroskedastisity test, and multicolinearity test). Research results are (1) teacher competency, teacher education, and learning language variable influence teacher performance of entire SMK town Karanganyar, shown by significant value as 0,000 < 0,05 and effective contribution as 55,8%. It shows that hypothesis of “teacher competency, teacher education and learning language variable influence school performance of entire SMK Town Karanganyar” is true. (2) teacher competency variable influences school performance of entire SMK Town Karanganyar shown by tvalue as 5,771 and significant level as 0,000. It shown that hypothesis of “teacher compentency variable influences school performance of entire SMK Town Karanganyar” is true. (3) teacher education variable influence to school performance of entire SMK Karanganyar Town shown by t count value as 5,480 and significant level as 0,000. It shows that hypothesis of “teacher education variable influences school performance of entire SMK in Karanganyar Town” is true. (4) learning languange variable influence to school performance of entire SMK in karanganyar sub district shown by t count value as 3,132 and significant level of 0,002. It shows that hypothesis of “learning languagevariable influences school performance of entire SMK in Karanganyar Town” is true.